A stable and flexible carbon black/polyethyleneimine‐bacterial cellulose photothermal membrane for high‐efficiency solar vapor generation. (9th June 2020) - Liu, Shang; Huang, Congliang
Summary: Although various special materials have been exploited for enhancing evaporation performance of a solar vapor generation system, their practical applications could be greatly limited by structure destruction due to the seawater corrosion and external mechanical forces. In this work, we have developed a carbon black/polyethyleneimine‐bacterial cellulose (CPB) membrane with vacuum filtration method to simultaneously enhance the strength and evaporation performance of solar vapor generation system, by applying carbon blacks as the photo‐thermal conversion material, bacterial cellulose as the skeleton material for enhancing the structure strength, and polyethyleneimine (PEI) for tailoring the water absorption capacity. Effects of carbon black particle concentrations and PEI concentrations were probed, respectively, for optimizing the light absorption capacity and water absorption capacity in laboratory. Furthermore, the outdoor experiments were carried out to evaluate the strength and evaporation performances of CPB membrane. Results show that the evaporation efficiency of the CPB membrane could reach about 85.05% and 81.89% in the lab and outdoor under one sun irradiation. Additionally, a force of 59.37 MPa and folding more than 100 times will not break the structure of CPB membrane, which confirms the preferable structure strength. This superior CPB membrane, together with its low cost, simple fabrication, excellent mechanical properties, scalability and desalination ability, provides a feasible way for practical applications. Abstract : A CPB photothermal membrane for high‐efficiency solar vapor generation.